Dihydroartemisinin-piperaquine versus artesunate-amodiaquine: superior efficacy and posttreatment prophylaxis against multidrug-resistant Plasmodium falciparum and Plasmodium vivax malaria. - Hasugian, A; Purba, H; Kenangalem, E; Wuwung, R; Ebsworth, E; Maristela, R; Penttinen, P; Laihad, F; Anstey, N; Tjitra, E; Price, R (2007)
BACKGROUND: Antimalarial drug resistance is now well established in both Plasmodium falciparum and Plasmodium vivax. In southern Papua, Indonesia, where both strains of plasmodia coexist, we have been conducting a series of studies to optimize treatment strategies. METHODS: We conducted a randomized trial that compared the efficacy and safety of dihydroartemisinin-piperaquine (DHP) with artesunate-amodiaquine (AAQ). The primary end point was the overall cumulative parasitological failure rate at day 42. RESULTS: Of the 334 patients in the evaluable patient population, 185 were infected with P. falciparum, 80 were infected with P. vivax, and 69 were infected with both species. The overall parasitological failure rate at day 42 was 45% (95% confidence interval [CI], 36%-53%) for AAQ and 13% (95% CI, 7.2%-19%) for DHP (hazard ratio [HR], 4.3; 95% CI, 2.5-7.2; P<.001). Rates of both recrudescence of P. falciparum infection and recurrence of P. vivax infection were significantly higher after receipt of AAQ than after receipt of DHP (HR, 3.4 [95% CI, 1.2-9.4] and 4.3 [95% CI, 2.2-8.2], respectively; P<.001). By the end of the study, AAQ recipients were 2.95-fold (95% CI, 1.2- to 4.9-fold) more likely to be anemic and 14.5-fold (95% CI, 3.4- to 61-fold) more likely to have carried P. vivax gametocytes. CONCLUSIONS: DHP was more effective and better tolerated than AAQ against multidrug-resistant P. falciparum and P. vivax infections. The prolonged therapeutic effect of piperaquine delayed the time to P. falciparum reinfection, decreased the rate of recurrence of P. vivax infection, and reduced the risk of P. vivax gametocyte carriage and anemia.